ANALISA OPTIMASI PORTOFOLIO YANG MEMUAT SAHAM-SAHAM KELOMPOK LQ45 - Liem Chin; Erwinna Chendra; Agus Sukmana (Universitas Katolik Parahyangan, 2015)
Abstract. Portfolio optimization is the process of choosing the proportions of various assets to be held in a portfolio in such way as to make the portfolio better than any other according to some criteria, e.g. minimize the risk and/or maximize the return. In this article, we will determine the proportions of each stock that optimizes the portfolio consisting of stocks in LQ45 index. We analyse the riskiest sector in LQ45 index, as well. LQ45 index was launched in February 1997. This index using 45 selected stocks with criteria specified by Indonesia Stock Exchange, among which are liquidity and market capitalization. The optimum criteria used in the portfolio are to minimize the risk with and without a particular return target. For both these criteria, short-selling is not allowed. We use Newton method to determine proportions that optimize the portfolio. We find that a portfolio that contains stocks from agriculture sector is the riskiest sector in LQ45 index whereas a portfolio that contains stocks from property sector gives the highest return.